The ability of 5% Tamarindus indica extract as cleaner of the root canal wall smear layer - Erawati Wulandari; Latief Mooduto; Theresia Indah Budhy S (Dental Journal (Majalah Kedokteran Gigi), 2007)
Tamarindus indica is one of traditional medicines. Pulpa tamaridorum consist of organic acid that is usually used as irrigant and to remove root canal wall smear layer. The aimed of this study was to elucidate the ability of 5% Tamarindus indica extract as a root canal irrigant to remove root canal wall smear layer. Eighteen tooth samples were cut on cervical line and divided into 2 then groups were prepared with K file and irrigated. Group 1 was irrigated by sterile aquabidest and group 2 was irrigated by 5% Tamarindus indica extract. Samples were cut longitudinally and formed 7 × 2× 2 mm specimen. Each specimen was photographed by scanning electron microscope, scored and summed. The total score obtained is used as the hygiene value of root canal wall. The collected data were statistically analyzed by using independent t test at 0.05 level. The result of the study showed there was a significant difference between 5% Tamarindus indica extract and sterile aquabidest (p < 0.05), the hygiene value of 5% Tamarindus indica extract was higher than sterile aquabidest. The conclusion of this investigation showed that 5% Tamarindus indica extract remove root canal wall smear layer.